Biolaw as an emerging discipline and linked to the demands of the modern world - Salcedo Hernández, José Ramón (2024)
Faced with the changes in humanity at a technological and techno-scientific level, the need arises for a systematic approach to biolaw, considering human dignity and survival of the entire ecosystem.